Penerapan Api Whatsapp Dalam Pelayanan Uji Plagiasi Universitas Bina Insan Berbasis Web Mobile - Fido Rizki; Davit Irawan; Asep Toyib Hidayat (STMIK Budi Darma, 2022)
Currently, the service for plagiarism testing or plagiarism testing at Bina Insan University is through a sending system using gmail, where this plagiarism test is carried out as a requirement for students to get a diploma, the file that is carried out for the plagiarism test is the result of the student's thesis which is made into a journal, software that used to check this plagiarism using the Turnitin service. Plagiarism checking itself is currently carried out by the LPPM section where the checking process is that students first send a journal from the results of the thesis that has been approved by the Supervisor to be tested for plagiarism, from the current system there are many obstacles and shortcomings including when sending using In gmail, there is often a buildup and irregularity of the existing data, which causes the process of checking student journals to be tested for plagiarism a little longer, not to mention that students rarely open their gmail to see the results that have been sent by the LPPM team. The solution that the author offers in this research is to create a new mobile web-based system, where this system will later be equipped with the Whatsapp API feature, the Whatsapp API acts as a liaison between the system and the user, where the way it works is that every process that has been carried out in the system automatically The Whatsapp API will automatically provide notifications both to students and the LPPM admin itself, the results obtained from this research are that the presence of the Whatsapp api can speed up and simplify the data collection and testing process that will be carried out.